Lingual hematoma, rare complication in a hemodialysis patient. A case presentation - Yuliel Varona Rodríguez (Medisur)
The case of a 78-years-old female patient with a chronic renal failure history under dialysis for nine years is presented. Four hours after finishing the hemodialysis, she began to experience pain in the oral cavity, a feeling of a busy mouth, and difficulty breathing. She was urgently transferred to the operating room where an emergency tracheostomy was performed due to lingual hematoma with extension to deep planes and compromised ventilation. This is an extremely rare complication that occurs frequently at the retropharyngeal or laryngeal level. Its appearance is potentially dangerous as it causes elevation of the floor of the mouth, obstruction of the airway and compromised ventilation. The presence of odynophagia and/or dysphagia in an anticoagulated patient should put the treating physician on alert; for this reason and because of the rarity of this situation, it was decided to publish the case.